Avaliação dos serviços públicos de endodontia nos centros de especialidades odontológicas de Minas Gerais - Jose Leonardo Barbosa Melgaco da Costa (2016)
Aim of this study was to evaluate Endodontics services in secondary care of the Dental Specialties Centers (DSC) of Minas Gerais (MG), during 2014. Outputs were collected from TABWIN, according to National Register of Health Establishment of the DSC of MG. Variables of municipalities characterization (population size, Human Development Index (HDI), Gini Index) and services (Family Health Program (FHP) coverage, accreditation, type of DSC, output) were extracted from the IBGE and DATASUS. Assessment of oral health managers of municipalities was done through a questionnaire. Descriptive analysis and Spearman correlation were performed, considering 5% significance level. Spread over 70 cities, 76 accredited DSC composed the sample, of which 65.8% were type II. Accreditation median time of DSC was 8 years. Most cities showed population size less than 50 thousand inhabitants (39.4%), HDI and Gini Index with 52.6% e 65.8%, respectively, above the median and 93.4% of the cities with FHP coverage above 50%. Single-rooted teeth endodontics showed the highest median production, followed by multi- and birradiculars teeth. Most DSC did not reach output target established by the Brazilian Ministry of Health (MofH) and 52.63% achieved targets in less than 25% of available months for analysis. There was a positive correlation, respectively, between a total of endodontic procedures and monthly mean of productivity and population size (p = 0.006; p = 0.003) and DSC type (p = 0.004; p = 0.001); besides of percentage of months with targets reached and population size (p = 0.015); and number of months with achieved target and number of available months for production analysis (p = 0.011). There was return of 94.29% of the managers' questionnaires, most had graduated in Dentistry (89.4%) and were more than two years in post (53%). Most cities had only one operating DSC (92.4%) with two dentists (30.3%). Endodontic treatments were performed exclusively in DSC (87.9%), and in 69.7% of DSC there was demand for endodontics assistance from other municipalities, being 59.1% from the same health microregion. There were referencing protocols from primary to secondary care in 87.9% of DSC, where 37.9% followed their own municipal protocol and 34.8% the MofH protocol. Most DSC had priorities list in attendance (65.2%) and 84.8% had one following output target, and 60.6% of these followed goals of MofH. In 50% of DSC, waiting time for start of endodontics was 1-6 months. Most DSC did not have technological resources (42%) to endodontic treatments and, after conclusion of endodontic treatment, 50% of patients were counter-referred to primary care. There was positive correlation between number of dentists that performed endodontic treatments in the DSC with total endodontics procedures (p = 0.013) and percentage of months with target reached (p = 0.029); and negative correlation between available technological resources with total endodontics procedures (p = 0.010) and percentage of months with target reached (p = 0.012). Most endodontics services in evaluated DSC did not achieve targets. It noted that some managers unaware principles of the MofH, demanding that management measures and targets must be reevaluated.